Tissue management in precision medicine: What the pathologist needs to know in the molecular era - Souza da Silva, Ricella; Pinto, Regina; Cirnes, Luis; Schmitt, Fernando (Frontiers in Molecular Biosciences, 2022)
Precision medicine is “an emerging approach for disease treatment and prevention that takes into account individual variability in genes, environment, and lifestyle for each person.” Among many medical specialists involved in precision medicine, the pathologists play an important and key role in the implementation and development of molecular tests that are in the center of decision of many therapeutic choices. Besides many laboratory procedures directly involved in the molecular tests, is fundamental to guarantee that tissues and cells collected for analysis be managed correctly before the DNA/RNA extraction. In this paper we explore the pivotal and interconnected points that can influence molecular studies, such as pre-analytical issues (fixation and decalcification); diagnosis and material selection, including the calculation of nuclei neoplastic fraction. The standardization of sample processing and morphological control ensures the accuracy of the diagnosis. Tissue or cytological samples constitutes the main foundation for the determination of biomarkers and development of druggable targets. Pathology and precision oncology still have a long way to go in terms of research and clinical practice: improving the accuracy and dissemination of molecular tests, learning in molecular tumor boards for advanced disease, and knowledge about early disease. Precision medicine needs pathology to be precise.